Answer:
1 and -1
Step-by-step explanation:
if a = -4 the equation= -1
if a = -3 the equation = 1
Step-by-step explanation:
|a+3|+|a+4|
If a = [-4,-3]
To solve the equation when a is -4
[tex]so \: we \: substitute \: a \: with \: - 4 \: then \: we \: solve \\ (a + 3) + (a + 4) \\ ( - 4 + 3) + ( - 4 + 4) \\ ( - 1) + (0) \\ = - 1[/tex]
That's the answer when a is -4
Now we solve for when a is -3
[tex](a + 3) + (a + 4) \\ ( - 3 + 3) + ( - 3 + 4) \\ (0) + (1) \\ = 1[/tex]
That's the answer when a is -3